Benedict's Prior: RB 65 - Kardong, Terrence (Cistercian studies quarterly, 2005)
The article presents information on the mimetic conflict theory of author Rene Girard. Specifically, he has tried to analyze violence by understanding its causes, its patterns, and its outcomes. While Girard's research started as a purely secular project, he soon concluded that religion has a big part to play in the dynamics of human violence. Unlike most critics, however, Girard does not think that religion is part of the problem; properly understood, religion should be part of the solution to violence. Instead of locating it in the realm of mythology as does the Book of Genesis, Girard finds it in the psychological phenomenon of mimesis or imitation. Simply put, people want what other people have or want. This looks very much like the capital sin of envy, but Girard takes it much further in his many books. Mimesis means that the object is desirable precisely because the other wants it or possesses it.